ANALISIS PERMINTAAN KREDIT PADA USAHA MIKRO DAN KECIL DI KECAMATAN MEDAN JOHOR - Taufan Achmad Felna; Wahyu Ario Pratomo (Ekonomi dan Keuangan, 2013)
The aim of this research is to analyze the factors that influencing micro entrepreneurs to ask loan from bank and to analyze the main factors that influencing their income. The data is obtained by direct interview and distributing questionnaires to 30 entrepreneurs in Subdistrict of Medan Johor. This research uses the descriptive method to reveal the profile of microenterprises and it also uses econometric analysis to the important factors to influence the income of entrepreneurs. The result shows that equity, credit and working hours influence entrepreneurs’ income. Keyword: micro enterprises, entrepreneur, entrepreneurship